The US shale revolution and the Arab Gulf States: The economic and political impact of changing energy markets - Kirsten Westphal; Marco Overhaus; Guido Steinberg (Stiftung Wissenschaft und Politik (SWP), 2014)
The US shale revolution is making a deep impact on the global energy markets, with the United States becoming self-sufficient in oil and gas and international flows shifting increasingly towards the Pacific region. But the Persian Gulf remains the backbone of the global oil markets, while its liquefied natural gas is of global strategic significance and a factor for energy supply diversification in Europe. Growing domestic energy security expands US policy options towards the Gulf states, whose regimes are already greatly unsettled by fears over an American pull-out. While there is as yet no sign of such a move, Europe must be prepared for greater burden-sharing with the United States, especially in relation to energy imports from the Gulf. Only in the long term and in interaction with political factors do developments in the energy markets have the potential to threaten the stability of the Arab Gulf states. In the short and medium term these countries will have to secure their own energy supplies while maintaining exports. They find themselves confronted with this challenge at a difficult juncture. Certainly, their existing socio-economic development model cannot simply be extrapolated into the future. The geopolitical imponderables in the Gulf region and the associated supply risks offer good grounds to push on with the German Energiewende (energy transition). At the same time the new energy map demands more international dialogue and closer cooperation. One starting point would be energy partnerships with the Gulf states. (SWP Research Paper)
Keywords: 320